Local and non‐local controls on a persistent cold‐air pool in the Arve River Valley. (14th April 2020) - Arduini, G.; Chemel, C.; Staquet, C.
Abstract: A numerical model is used to simulate a persistent cold‐air pool (PCAP) event that occurred in the section of the Arve River Valley around Passy in the French Alps. During this period, an upper‐level ridge from the Atlantic moved over Europe, allowing a PCAP to form and persist over time. The impact of the upper‐level ridge on the PCAP and on the dynamics within the valley section is quantified by examining the mass and heat budgets of the valley atmosphere. During the persistent stage, the magnitude of the flow through the tributary valleys is enhanced by the large‐scale flow. Also, the direction of the flow through one of the tributaries is found to be determined by the height of the PCAP with respect to that of the tributary above the valley floor. The tributary flows, together with subsiding motions at the valley top, control by and large the night‐time valley‐scale circulation and the thermal structure of the upper part of the PCAP, whereas thermally driven valley flows control its lower part. When the upper‐level ridge passes over the Arve River Valley, warm air advection through the tributaries continuously erodes the upper part of the PCAP during night‐time, thereby reducing its depth, while down‐valley flows export the air mass out of the valley. As the ridge moves away from the valley, the near‐surface air is found to be trapped within the valley. This trapping results from the advection of warm air in the upper part of the PCAP by the large‐scale flow channelled through one of the tributaries. This reduces the thermally induced pressure difference in the down‐valley direction, thereby suppressing the near‐surface down‐valley flow. The study therefore highlights the interplay between the large‐scale flow, the tributary flows and the thermal structure of the PCAP. Abstract : A numerical model using nested domains is used to simulate a persistent cold‐air pool (PCAP) event that occurred in February 2015 in the section of the Arve River Valley around Passy in the French Alps. (a) shows a topographic map of domain d02 with the positions of the nested domains d03, d04 and d05. (b) shows a topographic map of the innermost domain d05, with the dashed black polygon indicating the horizontal extent of the PASSY control volume. The study highlights the interplay between the large‐scale flow, the tributary flows and the thermal structure of the PCAP.